Exploring the Dynamic Dielectric Response of Yogurt Throughout Fermentation Across Frequencies Ranging from 10 to 3000 MHz - Singh, Rupinder Pal; Bansal, Namita; Singh, Amrit; Saroa, Amandeep; Mann, Kuldip Singh (Indian Journal of Dairy Science, 2025)
Our study delves into the intricate dielectric properties of yogurt, navigating its transformation during fermentation at 40°C and post-fermentation modulation across temperatures from 40°C to 10°C. Employing a sophisticated setup comprising a coaxial probe (Speag DAK-12, Schmidt & Partner Engineering AG, Switzerland) and a vector network analyzer (VNA) (Agilent Technologies, E5071C), operating seamlessly within the frequency spectrum of 10-3000 MHz, we meticulously examined yogurt’s behavior. Our findings unveil a compelling narrative: as yogurt undergoes fermentation, its pH gradually decreases from 6.5 to 4.3, inducing a remarkable escalation in the loss factor across all frequencies. This intriguing correlation between pH and loss factor underscores the intricate dynamics of yogurt’s fermentation process. The rich dataset gleaned from our investigation not only sheds light on the kinetics of yogurt gel formation but also holds promise for optimizing post-fermentation dielectric heat treatments, enhancing yogurt’s shelf life and ensuring its quality during storage.